A Step Towards Autonomous, Biomimetic, Non-GPS Based Navigation Methodology - Oyegbade, B. I.; Afolayan, M. O.; Umaru, S. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Global Positioning System (GPS) based navigations have their own inherent weakness; they can be overridden so easily and are not useful inside structures. One method of overcoming the above problem is the use of feature based navigation system. Nature has so much perfected this that copying nature is one of the best approaches available to scientist. In this study, desert ant (Cataglyphis fortis) was imitated. A simple infra-red based active beacons and robot mounted rotating receiver based on TSOP31138 infra-red sensor was implemented using New Three Objects Triangulation Algorithm (ToTAL) in its firmware for the robot pose. The designed robot with the triangulation algorithm was able to compute its pose such that on a grid of 6 m x 6 m, it can home to its base with a maximum error of 14.8 mm.